Morphological variations of the winged pearl oyster Pteria penguin (Roding, 1798) from South China Sea - Guo, Huayang; Zhang, Dianchang; Jiang, Shigui; Li, Youning; Zhang, Nan; Wang, Yu; Ma, Zhenhua (Indian Journal of Fisheries, 2017)
The present study was undertaken to evaluate the morphological variations of Pteria penguin (Roding, 1798) in wild as well as cultured populations from South China Sea. A total of 307 samples were collected from five different geographic locations comprising three wild (Pop. 1, 2 and 4) and two cultured (Pop. 3 and 5) populations and 10 measured traits were analysed. Principal component analysis (PCA), discriminant analysis and cluster analysis were used to evaluate the morphological variations in the collected samples. Results showed a low intra-population variation within the five sampled populations. Multivariate analyses indicated that the five populations were more or less differentiated on the basis of body characters, particularly those related to major dimensions of the shell outline and their ratios. Discriminant analysis revealed that the overall random assignment of individuals into their original groups was high (81.8%), indicating that these populations are highly divergent from each other. The proportion of individuals correctly classified into their original groups was 96.9, 76.7, 75.0, 78.0 and 82.0% for populations 1, 2, 3, 4 and 5 respectively. Cluster analysis showed highest morphological variation between Pop.1 and Pop. 2. All other populations (Pop.3, Pop.4 and Pop.5) were found to be morphologically similar and consistent with the respective geographical location. Results of the present study will be of use in resource assessment and management of P. penguin in the South China Sea.